Deklarasi Doha dalam Perspektif Akses Obat Murah dan Terjangkau: Sebuah Pelengkap Perjanjian TRIPS - Tomi Suryo Utomo (Unisia, 2007)
The Doha Declaration was developed after protests from developing and least developed countries asserting the TRIPS safeguards were unclear and ambiguous. Developing countries and least developed countries sought an interpretive tool for the TRIPS safeguards which fulfills the requirements of international law, in particular the Vienna Convention on the Law of Treaties and the legislative process of negotiation under the WTO decision making framework. Through the Doha Declaration, developing and least developed countries achieved their goal to clarify the TRIPS safeguards. The different level of economy, technology and interests among the members of the WTO will color the ongoing debate about the benefits of pharmaceutical patent protection under the WTO and effect upon access to essential medicines. The debate will reflect those favoring pro status quo for the TRIPS Agreement and the large number of countries which rely on the existence of the Doha Declaration. The outcome of this battle ends depends upon the willingness to seek the optimal solution for all.